Effect of different pre-treatment on the microstructure and intumescent properties of rice husk ash-based geopolymer hybrid coating - Abdullah, Mohd Na’im; Mustapha, Faizal; Ahmad, Kamarul Arifin; Mustapha, Mazlina; Khan, Tabrej; Singh, Balbir; Sebaey, Tamer A. (MDPI, 2022)
Despite the growing popularity of rice husk ash (RHA) in various applications, limited research has been devoted to identify the influence of silica content in RHA on the intumescent properties. The present work aims to introduce a novel and economical geopolymer hybrid fire retardant coating by utilizing the use of RHA. The silica from Rice husk (RH) was extracted using distilled water and hydrochloric acid as leaching agents and subjected to pyrolysis treatment. X-ray fluorescence (XRF) analysis indicated that RH that underwent HCl pre-treatment at 600 °C for one hour produced a high purity amorphous silica content of 93.92%. XRD measurements revealed that HCl pretreatment increased the crystallization temperature of RHA to 1000 °C and retained the amorphous state of silica for 2 h. In a fire resistance test, temperature at the equilibrium and time taken to reach 200 °C for sample S3 (93.92% wt. silica) showed 5.83% and 3.48% improvement compared to sample S1 (87.49% wt. silica). The microstructure analysis showed that sample S1 possessed bigger pores on the coating surface while an increment in silica content in sample S3 produced a dense foam structure. Results from a fire resistance test were supported by the Energy dispersive X-ray (EDX) analysis of the sample. The oxygen-to-carbon ratio of S1 and S3 coating samples were 1.695 and 1.622 respectively, which indicated that lower oxygen–to-carbon ratio in sample S3 coating resulted in better anti-oxidant properties. Interestingly, the increment of SiO2 content in RHA efficiently improved the compactness of the char layer, which resulted in a relatively higher fire-retardant efficiency. RHA proved to be a promising environmentally friendly strategy to replace halogenated fire retardant materials.